Ethnomathematic Exploration Of Cemetery Buildings Commander Khatib Kampar - Hafis, Muhammad Al; Hidayat, Adityawarman; Putra, Kasman Edi (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This research is qualitative research with an ethnographicapproach. The aim of this research is to determine the ethnomathematics of the Panglima Khatib Tomb Building. This research was conducted at the Panglima Khatib Kampar Tomb Building from September to October 2023. The Panglima Khatib Tomb Building is the tomb of one of the heroes of Kampar, namely Datuk Panglima Khatib. The methodused in thisresearch isdescriptive qualitative with an ethnographic approach, namely a type of research that describes and obtains data in a complete, comprehensive and in-depthmanner. The results of this research show that the mathematical concepts that exist in the Panglima Khatib Kampar Tomb Building are flat concepts such as squares, isosceles triangles, rectangles, rhombuses and circles. Spacebuilding concepts such as blocks and tubes. The concept of reflection or mirroring. And number concepts.